ROMANI/GYPSY WOMAN: SUBJECTIVE DIMENSION AND REALITY - Stefanovsky, Voria; Costa, Elisa (Revista Gênero e Interdisciplinaridade, 2025)
Reflection on the subjective dimension of being a Romani/Gypsy woman is the central axis that starts and guides this text. The proposal to decolonize and combat epistemological racism in academic practice is also carried over into the language used by the authors in the text, which includes poetry and the first person voice, and to the very process of intellectual construction of the same, which privileged the oral dialogue between two women who share common destinies and struggles and reflect on them. In the light of theories, but also of experiences, of scholars who also belong to the group to which they dedicate their work. Issues related to exclusion, anti-gypsyism, stereotypes and representations and the manifold subordination of Romani women are themes that permeate the discussions.